Electric stress and dielectric breakdown characteristics under high-frequency voltages with multi-harmonics in a solid-state transformer. (July 2021) - Wang, Weiwang; Wang, Xin; He, Jiefeng; Liu, Ying; Li, Shengtao; Nie, Yongjie
Highlights: Insulation of Solid-State Transformer is subjected to mixed-frequency electric stress. Dielectric breakdown decreases under mixed-frequency electric stress and high temperature. The high electric stress and dielectric loss under high frequency and harmonic voltages contribute to the low breakdown strength. Acceleration of electric breakdown under high frequency and temperature conditions probably happens. Abstract: Mixed-frequency electric stress and the thermal issue by rapid semiconductor switching and circuit topology cause the unexpected insulation breakdown, indicating a key issue on medium-high frequency (MF-HF) transformers. This work focuses on the effects of frequency and temperature on the breakdown strength of used epoxy resin insulation. An experimental method containing the power supply and breakdown measurement unit was constructed under high sinusoidal voltages with harmonic components. A continuous boost method was used to induce dielectric breakdown. Meanwhile, high voltage and current probes were employed to capture the breakdown voltage and current waveforms. The results indicate the reduction in the breakdown strength of the epoxy resin with the increase in frequency and temperature. Furthermore, the effects of temperature (up to 120 °C) on breakdown strength were no more obvious than those of frequency (up to 8 kHz). That is mainly derived from the glass transition of epoxy resin. Through discussing the dielectric loss and energy dissipation by FEM simulations together with the complex permittivity of epoxy resin, it could be concluded that the dielectric heating contributes to the acceleration of electric breakdown under high-frequency voltages. In addition to the fundamental frequencies, the harmonic voltages introduced high electric stresses and dielectric loss, resulting in a decrease in breakdown strength. The dielectric heating related to the electric stresses and frequencies should be considered in the insulation design of MF-HF transformers.